2015
DOI: 10.1080/08870446.2014.997731
|View full text |Cite
|
Sign up to set email alerts
|

Text2Plan: Exploring changes in the quantity and quality of action plans and physical activity in a text messaging intervention

Abstract: Although there were no differences in action planning or physical activity based on the content or tailoring of messages, the absence of text messages corresponded with declines in the quantity, but not the quality, of action plans. Furthermore, the quantity of action plans predicted changes in physical activity. Future research is needed to determine ways to facilitate sustained formation of multiple, specific action plans over the duration of action planning interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Future researchers in this area are encouraged to focus on developing mobile friendly web sites as Latinas are frequently accessing the Internet via smartphones [ 20 ]. Other aspects of smart phone technology (applications, text messaging) have been used to promote health behavior change in other groups [ 59 62 ] and should also be explored in this at risk target population. Such features could help drive participants to the website and improve utilization, resulting in even greater behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Future researchers in this area are encouraged to focus on developing mobile friendly web sites as Latinas are frequently accessing the Internet via smartphones [ 20 ]. Other aspects of smart phone technology (applications, text messaging) have been used to promote health behavior change in other groups [ 59 62 ] and should also be explored in this at risk target population. Such features could help drive participants to the website and improve utilization, resulting in even greater behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Creating restrictions on exactly when to decrease sedentary behavior may actually make the execution more complicated and harder to remember because it happens so frequently. However, very few studies have tested the effects of vague plans relative to specific plans (Mistry et al, 2015;de Vet, Oenema, & Brug, 2011). Another explanation may be that the situational cues in the stem of the intention items needed to be more specific to the SBQ in order to prompt heightened recognition and activation that typically occurs during implementation intention.…”
Section: Discussionmentioning
confidence: 99%
“…high commitment) was not surprising to see since the study assessed (but not did manipulate) students' current perceptions on sedentary behavior (Gollwitzer, 1999). It is also suggested that while specific plans may facilitate the quick and accurate identification of cues to action, vague plans allow for flexibility in the event that specific cues are not identified or missed (Mistry, Sweet, Rhodes, & Latimer-Cheung, 2015). Unlike other health behaviors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also had an opportunity to create their own text messages. Allowing for participant input into delivery of text messages is similar to other successful physical activity text message studies [ 57 , 58 , 60 ].…”
Section: Discussionmentioning
confidence: 99%